Successful thoracoscopic-assisted resection of a functional paraganglioma in the mediastinum with extracorporeal circulation: a case report - Zhihui Yang; Xiaojie Huang; Danting Zhou; Tao Tang; Hengxing Liang; Wenliang Liu; Fenglei Yu; Chen Chen (Journal of Cardiothoracic Surgery)
Abstract Background Paragangliomas are rare neoplasms arising from extra-adrenal chromaffin cells, with mediastinal paragangliomas representing an exceptionally rare subset. This report details the surgical management of a complex mediastinal paraganglioma case, presenting with refractory hypertension and invasion of critical surrounding structures. A comprehensive review of the current literature is included to underscore existing cases, enhance clinical awareness, and share our insights and experience in the diagnosis and treatment of this challenging condition. Case presentation A 16-year-old female presented with recurrent headaches and persistent hypertension lasting over one year. Based on clinical findings and imaging studies, she was preliminarily diagnosed with a mediastinal paraganglioma. The patient underwent comprehensive preoperative management, including oral α- and β-adrenergic blockade, preoperative arterial embolization, and intravenous fluid volume expansion, to optimize endocrine control. Thoracoscopic resection of the mediastinal mass was initially attempted; however, the procedure became complex due to the high risk of uncontrolled hemorrhage and invasion of adjacent vital structures. Following the preoperative surgical plan, the incision was converted to a lateral thoracotomy, and cardiopulmonary bypass was initiated. Meticulous dissection enabled the complete removal of the tumor along with the affected posterior wall of the left atrium, followed by reconstruction of the left atrium and the right pulmonary vein. The surgery was successfully completed, and follow-up assessments showed no signs of tumor recurrence or metastasis. Conclusions Functional mediastinal paraganglioma is a rare neuroendocrine tumor, with complete surgical resection being the gold standard treatment. Stringent perioperative management is crucial to mitigate the risk of cardiovascular complications associated with functional tumors. Lifelong surveillance is recommended to detect potential recurrence or metastasis. Effective collaboration within a multidisciplinary team is essential for ensuring accurate diagnosis and delivering optimal, individualized care.